THE EFFECT OF EPS, ROA, DIVIDEND AND INFLATION ON STOCK PRICES IN FINANCIAL SECTOR COMPANIES LISTED ON IDX FOR THE 2015-2019 PERIODS - Maya Sabirina Panggabean; Clara Clara; Vidya Natalie; Fanny Fanny; Vanessa Titania (Riset Akuntansi Keuangan, 2021)
This study intends to explore and analyze how the relevance between EPS,ROA, Dividends and Inflation on stock prices in financial sector companies in2015-2019. This test method uses a quantitative approach, with quantitativedescriptive type of testing and uses multiple linear regression methods.Population of 91 companies with purposive sampling method, obtained totalsample of 120 from 24 companies. Based on the test results, it can beconcluded that simultaneously EPS, ROA, Dividend and Inflation have asimultaneous and positive effect on stock prices., it is obtained Fcount138.822> Ftable 2.451. Partially, EPS has a positive effect on stock prices,the results obtained are Tcount 7,215> Ttable 1,981 and sig. 0.000 <0.05compared to ROA has a negative effect on stock prices, the results obtainedare Tcount -4.053 <Ttable -1.981 and the sig value. 0.000 <0.05. Dividend resultsobtained Tcount 1.621 <Ttable 1.981 and sig.0.108> 0.05 for inflation, the resultsobtained Tcount -0.597> Ttable -1.981 and sig value. 0.552> 0.05.